2013
DOI: 10.1111/cas.12093
|View full text |Cite
|
Sign up to set email alerts
|

Bone morphogenetic protein‐9 induces epithelial to mesenchymal transition in hepatocellular carcinoma cells

Abstract: Epithelial-mesenchymal transition (EMT) is an important mechanism to initiate cancer invasion and metastasis. Bone morphogenetic protein (BMP)-9 is a member of the transforming growth factor (TGF)-b superfamily. It has been suggested to play a role in cancer development in some non-hepatic tumors. In the present study, two hepatocellular carcinoma (HCC) lines, HLE and HepG2, were treated with BMP-9 in vitro, and phenotypic changes and cell motility were analyzed. In situ hybridization (ISH) and immunohistochem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
69
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(74 citation statements)
references
References 47 publications
4
69
1
Order By: Relevance
“…BMPs have been described as either inhibitors of endMT (BMP7 in cardiac fibrosis) (26) or inducers of endMT [BMP6 in cerebral cavernous malformations (27) and BMP2 in cardiac valve formation (28)]. BMP9 has been recently shown to induce EMT in hepatocellular carcinoma cells (29), and our data support that BMP9 and BMP10 can also induce endMT.…”
Section: Discussionsupporting
confidence: 75%
“…BMPs have been described as either inhibitors of endMT (BMP7 in cardiac fibrosis) (26) or inducers of endMT [BMP6 in cerebral cavernous malformations (27) and BMP2 in cardiac valve formation (28)]. BMP9 has been recently shown to induce EMT in hepatocellular carcinoma cells (29), and our data support that BMP9 and BMP10 can also induce endMT.…”
Section: Discussionsupporting
confidence: 75%
“…In line with this, we confirmed enhanced BMP4 expression and its correlation with aggressive tumour growth in human HCC tissues 4. Most recently, Li et al 5 identified that enhanced BMP9 expression induces epithelial to mesenchymal transition and herewith invasiveness of HCC cells in vitro . Besides HCC, Nakatsuka et al 6 reported transient expression of BMP2 and BMP4 in acute liver injury.…”
Section: Introductionsupporting
confidence: 87%
“…These proteins have been related to EMT regulation and cellular differentiation 22, 23, 24, 25. Nt2 was centered on NFkB and involved genes such as NFkB early‐response gene IER3, secreted signaling molecules bone morphogenetic protein (BMP), and TF ETS homologous factor (EHT) that belongs to an ETS TF subfamily characterized by epithelial‐specific expression and which may be involved in epithelial differentiation and carcinogenesis 26, 27, 28, 29. Nt3 was closely related to cancer and cellular movement being involved with the WNT pathway and ‘cadherin switch’ (repression of E‐cadherin and expression of N‐cadherin).…”
Section: Discussionmentioning
confidence: 99%